Pentraxins in Complement Activation and Regulation - Ma, Ying Jie; Garred, Peter (Frontiers in Immunology, 2018)
The complement is the first line of immune defense system involved in elimination of invading pathogens and dying host cells. Its activation is mainly triggered by immune complexes or pattern recognition molecules (PRMs) upon recognition against non-self or altered self-cells, such as C1q, collectins, ficolins and properdin. Recent findings have interestingly shown that the pentraxins (C-reactive protein, CRP; serum-amyloid P component, SAP; long pentraxin 3, PTX3) are involved in complement activation and amplification via communication with complement initiation PRMs, but also complement regulation via recruitment of complement regulators, for instance C4b binding protein (C4BP) and factor H (fH). This review addresses the potential roles of the pentraxins in the complement system during infection and inflammation, and emphasizes the underlining implications of the pentraxins in the context of complement activation and regulation both under physiological and pathological conditions.